Drama Jalan Mutiara Karya Sitor Situmorang: Perspektif Eksistensialisme Jean Paul Sartre - Khudzaifi, Ilham; Jiwa Atmaja, I Made; Suarsa, I Made (Humanis, 2016)
The object of this study is Jalan Mutiara drama by Sitor Situmorang which are consists of three stories, namely Jalan Mutiara, Pertahanan Terakhir and Pulo Batu. This research focuses on two problems, they are drama structure that consisting of premise, character and plot, moreover the actualization of existentialism thought of the Satrenism in those dramas. The analysis of Jalan Mutiara drama showed the premise of the story, the premise of this drama is disappointed to the character of Elizabeth, the story of Pertahanan Terakhir is a rebellion, and the story of Pulo Batu is about betrayal, love and the throne. In addition the plot used in those stories are forward and backward plot. The characters of those stories clearly defined in terms of sociological and psychological, unfortunately lack in terms of physiological. The existentialism of Jean Paul Sartre cult proved to be actualized through the characters that exist in the three stories of Jalan Mutiara drama by Sitor Situmorang.